Writing prayers: apotropaic languages at Dead Sea Scrolls (Revista Archai, 2022)
The problem of how to protect yourself from harm is a recurrent theme in many historical periods and societies. Jewish apotropaic texts, particularly in the Second Temple period, bring a variety of languages associated with protection. This article delineates the different apotropaic languages described in the Dead Sea Scrolls, focusing on the use of writing as a way of recording and preserving prayers.